The S2 gene nucleotide sequences of prototype strains of the three reovirus serotypes: characterization of reovirus core protein sigma 2. - Dermody, T S (1991)
The S2 gene nucleotide sequences of prototype strains of the three reovirus serotypes were determined to gain insight into the structure and function of the S2 translation product, virion core protein sigma 2. The S2 sequences of the type 1 Lang, type 2 Jones, and type 3 Dearing strains are 1,331 nucleotides in length and contain a single large open reading frame that could encode a protein of 418 amino acids, corresponding to sigma 2. The deduced sigma 2 amino acid sequences of these strains are very conserved, being identical at 94% of the sequence positions. Predictions of sigma 2 secondary structure and hydrophobicity suggest that the protein has a two-domain structure. A larger domain is suggested to be formed from the amino-terminal three-fourths of sigma 2 sequence, which is separated from a smaller carboxy-terminal domain by a turn-rich hinge region. The carboxy-terminal domain includes sequences that are more hydrophilic than those in the rest of the protein and contains sequences which are predicted to form an alpha-helix. A region of striking similarity was found between amino acids 354 and 374 of sigma 2 and amino acids 1008 and 1031 of the beta subunit of the Escherichia coli DNA-dependent RNA polymerase. We suggest that the regions with similar sequence in sigma 2 and the beta subunit form amphipathic alpha-helices which may play a related role in the function of each protein. We have also performed experiments to further characterize the double-stranded RNA-binding activity of sigma 2 and found that the capacity to bind double-stranded RNA is a property of the sigma 2 protein of prototype strains and of the S2 mutant tsC447.